Exploring attributes for an authentic Christian spirituality in an age of growing secularization and scepticism: A practical theological reflection - Dames, Glenda Alma (Stellenbosch Theological Journal, 2023)
The focus of the article is to highlight authentic exponents of the Christian faith and to elicit the attributes of Christian spirituality. The first goal is to provide a backdrop of current notions and applications of spirituality and its impact on Christian spirituality. Secondly, to conceptualise spirituality in a universal sense. Thirdly, to examine spirituality within a Christian framework. With reference to the Christian context, biblical and theological resources such as the theology of Thurneysen (1963), Chmielewski (2017) and Ridderbos (1962), amongst others, will be applied. Biblical texts and leading authors on Christian spirituality will also be consulted. From these conceptualisations an analysis will be made regarding the different attributes of spirituality generically, and Christian spirituality, specifically. The methodological approach will be from a Christian hermeneutic perspective. Finally, conclusions will be made to highlight the findings regarding the features of authenticity and its link to attributes of Christian spirituality today.